Intraguild Predation or Spatial Separation? The efficacy and Interactions of Two Natural Enemy Species for the Biological Control of Pear Psyllid (Cacopsylla pyri) - Laura A. Reeves; Michelle T. Fountain; Michael P. D. Garratt; Deepa Senapathi (Journal of Insect Behavior, 2024)
Pear psyllid ( Cacopsylla pyri ) is a persistent pest to the pear industry; with an estimated cost of £5 million per annum in the UK alone. This phloem feeding insect is resistant to a large proportion of approved pesticides, necessitating the use of alternative control strategies. Many pear growers practice integrated pest management (IPM) of pear psyllid, focusing on maximizing natural enemy populations, whilst minimizing the use of agrochemical sprays. The anthocorid Anthocoris nemoralis and the European earwig Forficula auricularia are particularly effective at controlling pear psyllid populations during the summer months. Despite the effectiveness of both natural enemies, there is a lack of understanding on whether both species should be promoted together or separately, due to the risk of intraguild predation (IGP) or interference competition. Furthermore, abiotic factors including temperature may influence both behaviors, altering activity level and niche overlap. Although IGP and interference competition have been documented between multiple species of natural enemies neither have been studied between these two specific predators. Using microcosm experiments, olfactometer assays and survival analyses this study demonstrated whether A. nemoralis and F. auricularia can be used in synchrony to control pear psyllid. Results indicated that IGP is present; F. auricularia will consume A. nemoralis when predators are not spatially separate and in absence of psyllid prey. There was no evidence for interference competition, although both predators consumed more prey at higher temperatures. This confirms that pear growers can encourage both predators for the control of pear psyllid without losing predation efficacy.

Functional and Behavioral Responses of the Natural Enemy Anthocoris nemoralis to Cacopsylla pyri, at Different Temperatures - Laura A. Reeves; Michael P. D. Garratt; Michelle T. Fountain; Deepa Senapathi (Journal of Insect Behavior, 2023)
Anthocoris nemoralis is the dominant predator of pear sucker ( Cacopsylla pyri ) in the UK. Anthocoris nemoralis migrates into orchards in spring or is introduced as a biocontrol agent, reaching peak population levels in July-August, contributing to effective control of summer pear sucker populations. However, due to temperature dependent development and metabolism there are concerns that C. pyri populations or feeding rates may increase due to changing climatic conditions. Thus, how A. nemoralis responds to temperature, impacts its ability as a biocontrol agent. Functional response assays, monitoring attack rate and handling time of A. nemoralis and behavioral assays, using Ethovision tracking software occurred, to assess the impact of temperature on predation. Experiments were conducted at current and future July-August mean temperatures, predicted using RCP4.5 and RCP8.5 (medium and high, representative concentration pathway) emissions scenarios, using 2018 UK Climate Projections (UKCP18). All treatments demonstrated a Type II functional response, with female anthocorids demonstrating shorter handling times and higher attack rates than males. Males showed longer prey handling times at 18 °C compared to 23 °C and more time was spent active at lower temperatures for both sexes. Females did not show significant differences in attack rate or handling time in response to temperature. Overall prey consumption was also not significantly affected by temperature for either sex. This study suggests that anthocorids are likely to remain effective natural enemies under future predicted temperatures, due to non-significant differences in prey consumption.

The Role of Olfactory Cues in Short-Range Mate Finding by the Emerald Ash Borer, Agrilus planipennis Fairmaire (Coleoptera: Buprestidae) - Deepa S. Pureswaran; Therese M. Poland (Journal of Insect Behavior, 2009)

Is Bigger Better? Size and Pheromone Production in the Mountain Pine Beetle, Dendroctonus ponderosae Hopkins (Coleoptera: Scolytidae) - Deepa S. Pureswaran; John H. Borden (Journal of Insect Behavior, 2003)